2021
DOI: 10.1007/s00127-021-02025-9
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on the COVID-19 pandemic and its divergent effects on social participation and mental health across different study groups with and without mental disorders

Abstract: Purpose With the rapid spread of COVID-19 and the restrictions imposed in many parts of the world, there is growing concern about its impact on mental health. This longitudinal study investigated the social participation, social inclusion and psychological well-being in adults with and without mental disorders before the beginning of the pandemic, as well as during and after strict lockdown restrictions in Germany. Methods The sample (n = 106) consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 23 publications
6
51
2
2
Order By: Relevance
“…Contrary to public health concerns initially raised about psychological distress increasing during the COVID-19 pandemic (Zhang et al, 2020) and findings from some studies showing heightened psychological distress during the pandemic's initial wave (Devaraj & Patel, 2020;Shechter et al, 2020;Xiong et al, 2020), results from our current study indicated that mental health problems remained stable from pre-pandemic baseline in December 2019/January 2020 and across the first two COVID-19 pandemic waves. Though surprising, these findings are consistent with stable patterns of psychological distress identified in some other studies conducted during the first pandemic wave (Mergel & Schützwohl, 2021;Qiu et al, 2020;Wang et al, 2020;Zhou et al, 2020). Our findings may also be reflective of similar patterns identified in other longitudinal studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Contrary to public health concerns initially raised about psychological distress increasing during the COVID-19 pandemic (Zhang et al, 2020) and findings from some studies showing heightened psychological distress during the pandemic's initial wave (Devaraj & Patel, 2020;Shechter et al, 2020;Xiong et al, 2020), results from our current study indicated that mental health problems remained stable from pre-pandemic baseline in December 2019/January 2020 and across the first two COVID-19 pandemic waves. Though surprising, these findings are consistent with stable patterns of psychological distress identified in some other studies conducted during the first pandemic wave (Mergel & Schützwohl, 2021;Qiu et al, 2020;Wang et al, 2020;Zhou et al, 2020). Our findings may also be reflective of similar patterns identified in other longitudinal studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings may also be reflective of similar patterns identified in other longitudinal studies (e.g. Daly & Robinson, 2021;Fancourt et al, 2021;Mergel & Schützwohl, 2021;Pierce et al, 2021;Varga et al, 2021), in which heightened psychological distress during the very earliest stages of the pandemic was followed by a gradual decrease in problems as the first pandemic lockdown progressed. Distress then gradually plateaued at a lower rate as lockdown restrictions eased.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations